Risk of Being Born Preterm in Offspring of Cancer Survivors: A National Cohort Study - Huang, Wuqing; Sundquist, Kristina; Sundquist, Jan; Ji, Jianguang (Frontiers in Oncology, 2020)
Background: With the increased number of cancer survivors, it is necessary to explore the effect of cancer and its treatments on pregnancy outcomes, such as preterm birth, which seriously endangers the health of offspring. We aimed to explore the risk of being born preterm among offspring of cancer survivors. Materials and methods: This is a retrospective cohort study. All singleton live births between 1973 and 2014 in Sweden with information of birth outcomes were retrieved from the Swedish Medical Birth Register. By linking to several Swedish registers, we identified all parents of children and parental cancer diagnosis. Logistic regression was used to estimate odds ratios and 95% confidence intervals. Results: As compared to the children without parental cancer, the risk of being born preterm was significantly higher among children of overall female cancer survivors born after cancer diagnosis with an adjusted OR of 1.48 (95 CI% = 1.39-1.59), in particular those diagnosed with childhood cancer and cancer in female genital organs. And the risk might continuously decline with time at the first eight years after maternal diagnosis. A higher risk of being born preterm was found among offspring of male survivors diagnosed with central nervous system cancer (Adjusted OR=1.26, 95% CI =1.04-1.53). Conclusions: Our study provides evidence for a higher risk of being born preterm among children of female cancer survivors and male survivors with central nervous system tumour, as well as indicates that the effect on female reproductive system from cancer and related-treatments might decline with time.